Idiopathic pulmonary haemosiderosis in a child with Down’s syndrome: case report and review of the literature - Aceti, A.; Sciutti, R.; Bracci, et al., P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
We report the case of a female child with Down’s syndrome affected by idiopathic pulmonary haemosiderosis (IPH), who was successfully treated with hydroxychloroquine. First-line conventional treatment of IPH is traditionally based on systemic corticosteroids; however, many steroid-sparing agents are being increasingly used as adjuncts to corticosteroids in children with recurrent or refractory bleeding. The use of these drugs is particularly promising for maintenance treatment, because it tends to avoid the adverse effects of longterm corticosteroids.